Lessons from the genomic analysis of Hesperiidae (Lepidoptera) holotypes in the MIZA collection (Maracay, Venezuela) - Zhang, Jing; Cong, Qian; Shen, Jinhui; Song, Leina; Orellana, Andrés; Brockmann, Ernst; Mielke, Carlos G. C.; Mielke, Olaf H. H.; Costa, Mauro; Grishin, Nick V. (Zootaxa, 2023)
Genomic sequencing and analysis of holotypes from the MIZA collection (Maracay, Venezuela) and their comparison with other species and their type specimens advances our understanding of their taxonomy. Jemadia demarmelsi Orellana, [2010] is confirmed as a species-level taxon and its female is genetically verified. The following are species-level taxa, not subspecies: Amenis pedro O. Mielke & Casagrande, 2022, stat. nov. (not Amenis pionia (Hewitson, 1857)) and Jemasonia sosia (Mabille, 1878), stat. rest. (not Jemasonia hewitsonii (Mabille, 1878)). Amenis ponina rogeri Orellana, [2010], stat. nov. and Jemasonia pater ortizi (Orellana, [2010]), stat. nov. are subspecies, not species. Jemadia pseudognetus imitator (Mabille, 1891), comb. nov. (not Jemadia hospita (Butler, 1877)) and Damas cervelina Orellana & Costa, 2019, comb. nov. (not Megaleas Godman, 1901) are new combinations.